PEMBERDAYAAN EKONOMI PEREMPUAN MELALUI PROGRAM INKUBASI KEWIRAUSAHAAN UNTUK PENGUATAN USAHA MIKRO DI KOTA MALANG - Fika Fitriasari; Nurul Asfiah; Rohmat Dwi Jatmiko; Aan Fardani Ubaidillah (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2026)
This community service program aims to empower women managing micro-enterprises in Malang City through an entrepreneurial incubation initiative. The primary focus of the program includes strengthening digital marketing and human resource management to enhance economic independence. The target partners previously faced challenges, including limited marketing technology and inefficient operational management. Through intensive training and mentoring, participants were guided to optimize business management and expand market access via social media and marketplaces. The implementation method was carried out systematically through socialization, continuous training, and participatory mentoring. The results of the activity demonstrate positive achievements, including a 20% increase in sales volume and 60% of participants successfully establishing a consistent brand identity. In the managerial aspect, more than 60% of participants demonstrated improved capabilities in structured business planning, data-driven decision-making, and clearer task delegation. The integration of digital marketing mastery and human resource management proved effective in increasing production capacity and the self-confidence of women entrepreneurs. Overall, this program successfully transformed the partners' mindset from conventional management to professional, technology-adaptive management. This success serves as a vital foundation for the long-term economic strengthening of women in Malang City.